2001
DOI: 10.1523/jneurosci.21-05-01490.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Domain Mutations of the L1 Cell Adhesion Molecule Reduce L1–Ankyrin Interactions

Abstract: The neural adhesion molecule L1 mediates the axon outgrowth, adhesion, and fasciculation that are necessary for proper development of synaptic connections. L1 gene mutations are present in humans with the X-linked mental retardation syndrome CRASH (corpus callosum hypoplasia, retardation, aphasia, spastic paraplegia, hydrocephalus). Three missense mutations associated with CRASH syndrome reside in the cytoplasmic domain of L1, which contains a highly conserved binding region for the cytoskeletal protein ankyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 33 publications
6
76
0
Order By: Relevance
“…shown that the cytoplasmic SFI GQY motif of L1CAM (aa 1224-1229, which is present in all L1CAM family members and is highly conserved from invertebrates to vertebrates) is essential for ankyrin binding (Garver et al, 1997;Needham et al, 2001). By introducing two pathological missense mutations, namely S1224L and Y1229H, reduced recruitment of ankyrin to the plasma membrane in vitro was observed (Needham et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…shown that the cytoplasmic SFI GQY motif of L1CAM (aa 1224-1229, which is present in all L1CAM family members and is highly conserved from invertebrates to vertebrates) is essential for ankyrin binding (Garver et al, 1997;Needham et al, 2001). By introducing two pathological missense mutations, namely S1224L and Y1229H, reduced recruitment of ankyrin to the plasma membrane in vitro was observed (Needham et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…By introducing two pathological missense mutations, namely S1224L and Y1229H, reduced recruitment of ankyrin to the plasma membrane in vitro was observed (Needham et al, 2001). Knock-in mice expressing the missense mutation Y1229H exhibit mistargeting of mutant ganglion cell axons from the ventral retina to lateral sites in the contralateral superior colliculus (Buhusi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated two L1 mutants, either lacking the intracellular domain except for the membrane proximal KRS sequence (L1trun) or with the mutation tyrosine 1229 to histidine (L1YH) known to abolish ankyrin binding (32). In 293T cells expressing the truncated form of L1 lacking the intracellular domain (L1trun), basal shedding was found to be strongly increased compared with the full-length form of L1 (L1wt).…”
Section: Discussionmentioning
confidence: 99%
“…L1-CAM-ankyrin interactions are regulated by tyrosine phosphorylation at the conserved ankyrin binding site in the L1-cytoplasmic tail (comprised of the amino acid sequence FIGQY); tyrosine to histidine substitutions at this site inhibit L1-mediated recruitment of ankyrin to the cell membrane (Zhang et al, 1998;Needham et al, 2001;Gil et al, 2003). Similarly, the activation of receptor-tyrosine kinases by their ligands drives indirectly the phosphorylation of the FIGQY tyrosine in vertebrate L1-family members and inhibits L1-CAM-ankyrin interactions, suggesting that phosphorylation plays a central role in the regulation of ankyrin binding to L1-CAM Gil et al, 2003).…”
Section: Introductionmentioning
confidence: 99%